Legal Regulations Related to Odour Nuisance (Current State of the Law and Proposed Changes) - Folgier, Anna (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Odour nuisance is a subjective state of discomfort experienced by an individual at the physical and psychical level, caused by the smell of a substance occurring in the air. As emphasized in scholarly literature, odour nuisance is one of the most common cause of complaints submitted to organs of Environmental Protection Inspectorate. Nevertheless, for the time being there is no legal act under Polish law and in the EU legal system that would comprehensively regulate issues related to combatting odour nuisance. The paper attempts at analysing legal acts concerning the discussed issues that have so far been issued by the Ministry of the Environment, as well as the bill of the statute on minimal distance applicable to a planned undertaking within agricultural sector whose operation may involve a risk of odour nuisance, as it stood on 5 May 2021. The paper also indicates statutory regulations that indirectly relate to restrictions on odour nuisance. The dogmatic legal research method was used to carry out the analysis.